2017
DOI: 10.4172/2157-7420.1000262
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Apps for Education and Practice

Abstract: The smartphone, bringing together the communication and information technologies, is a device that offers an easily and friendly access to the information. Mobile health applications (apps) are increasing popular and could become an integral part of our daily lives, no matter if we are students or health care professionals. Having the support and agreement of the leadership of the hospitals and health institutions, the nurse community is starting to use this technology in many different areas. The goal of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Theron et al [ 110 ] (p.154) observed that “nurses use information and knowledge to inform practice and to educate individuals, families and communities with information that will assist them in making healthcare decisions that will positively impact their quality of life”. Therefore, knowledge and understanding of digital information are necessary for undergraduate nursing curricula to prepare graduates for an increasingly digital workplace [ 111 , 112 , 113 , 114 ]. As Brown et al [ 109 ] (p. 457) observed, “It is imperative that curricula are developed and implemented so that students’ pre-existing and everyday digital literacy can be further developed, enhanced, and transposed to the bedside”.…”
Section: Discussionmentioning
confidence: 99%
“…Theron et al [ 110 ] (p.154) observed that “nurses use information and knowledge to inform practice and to educate individuals, families and communities with information that will assist them in making healthcare decisions that will positively impact their quality of life”. Therefore, knowledge and understanding of digital information are necessary for undergraduate nursing curricula to prepare graduates for an increasingly digital workplace [ 111 , 112 , 113 , 114 ]. As Brown et al [ 109 ] (p. 457) observed, “It is imperative that curricula are developed and implemented so that students’ pre-existing and everyday digital literacy can be further developed, enhanced, and transposed to the bedside”.…”
Section: Discussionmentioning
confidence: 99%
“…Theron et al [107] (p.154) observed that "nurses use information and knowledge to inform practice and to educate individuals, families and communities with information that will assist them in making healthcare decisions that will positively impact their quality of life". Therefore, knowledge and understanding of digital information are necessary for undergraduate nursing curricula to prepare graduates for an increasingly digital workplace [108][109][110][111]. As Brown et al [106] (p.457) observed "It is imperative that curricula are developed and implemented so that students' preexisting and everyday digital literacy can be further developed, enhanced, and transposed to the bedside".…”
Section: Implications Of the Digital Native Narrative On The Digital ...mentioning
confidence: 99%
“…Sin embargo, la estructura modular de estas tres variedades de códigos es similar y solo se diferencian entre sí por la forma de ejecutar la acción al ser decodificados. Independientemente del tipo de funcionalidad, si un código se encuentra dañado físicamente, sucio o están interrumpidos los patrones o cuadros de alineación el código no se podrá leer (3,6,7,9).…”
unclassified